Additional analysis of mtDNA from the Tommy and Mine Canyon sites. (June 2017) - Snow, Meradeth; Durand, Kathy; Gustafson, Martha; Smith, David Glenn
Abstract: Ancient mitochondrial DNA analysis of samples from the Chaco outlier Tommy and Mine Canyon sites (dating to PII and PIII, respectively, and located near Farmington, New Mexico) originally revealed distinctly different haplogroup frequency distributions from one another. An additional twelve samples were added to those already published (Snow et al., 2010), bringing the total number of individuals with mitochondrial DNA data to 60. The additional samples diminished this difference but maintained the statistically significant distinction between the sites, pointing to a potential sampling bias at the Mine Canyon Site that might explain some, but not all, of the difference. The sites were compared with those from both modern and prehistoric populations in the desert Southwest and Mexico to better understand the regional context of the inhabitants, as well as inter-regional relationships, demonstrating that the Tommy Site fits well within the general Southwestern pattern, while the Mine Canyon Site stands out due to its higher than normal frequency of haplogroup A2. Thirteen burials from a kiva structure at the Mine Canyon Site are compared to the remainder of the excavated burials from the site in terms of mtDNA, burial position, pathology, and grave goods. The statistically significant differences of the kiva burials are discussed in terms of possible evidence of site abandonment, disease, slavery, and witchcraft. Highlights: mtDNA from two sites in the US Southwest are discussed in context of migration. mtDNA from the Southwest shows shared maternal ancestry with Zuni and Chumash. mtDNA from kiva interments demonstrates shared maternal ancestry among members.